Utilização da modelagem sistêmica para analisar o efeito da variação climática no parâmetro produtividade da água na laranja Natal (Citrus sinensis L. Osbeck) no Estado de São Paulo - Pereira, Francisca Franciana Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main objective of the research was to develop a model based on dynamic systems aided by STELLA software. The study hypothesis was that: the climate variations, specifically CO2 concentrations and changes in air temperature will produce different effects on the water productivity parameter, increasing or decreasing water use efficiency by the Natal orange. The model was developed through a systematic analysis of the factors that interfere in the formation of crop biomass. It was determined as main variables: CO2, air temperature, transpiration, precipitation, water deficit, irrigation water depth, canopy cover and their interrelations. The structure was represented in a causal diagram and from this, it was developed the stocks and flows diagram. The later established the mathematical relationships between the model's variables enabling numerical simulation. The time step used for the simulations and applied was determined by the crop cycle, allowing a time frame from 2010 to 2100. The model has all the variables that are being able to be quantified, pursuing results closer to reality. In general, the results of the developed model showed that the rising of CO2 concentrations in the atmosphere combined with higher temperatures will promote greater efficiency of water use by this orange variety. Other factors were added such soil water deficit; it was verified that a reduction in the water productivity parameter for non-irrigated condition will be considerably higher than the irrigated condition by 2100. In the irrigated area the model presents, on all quantities of CO2 projected by the Intergovernmental Panel on Climate Changes - IPCC, higher values for water productivity parameter and it also in the reduction rates of CO2 assimilation as a function of air temperature. It was concluded that the model, here presented, was able to determine the influence of climate, especially future CO2 ...

O objetivo principal da pesquisa foi desenvolver um modelo de simulação dinâmica fundamentado nos princípios da Dinâmica de Sistemas auxiliado pelo software STELLA. A hipótese do estudo foi que: as variações no clima, mais especificamente as concentrações de dióxido de carbono (CO2) e as alterações na temperatura do ar, gerarão diferentes efeitos no parâmetro de produtividade da água, aumento ou diminuição na eficiência e uso da água pela laranjeira Natal (Citrus sinensis L. Osbeck). O modelo foi desenvolvido através de uma análise sistêmica dos fatores que interferem no processo de formação da biomassa das culturas. Foram determinadas as principais variáveis como: CO2, temperatura do ar, transpiração, precipitação, déficit hídrico, lâmina de irrigação, volume de copa e suas respectivas inter-relações. A estrutura foi representada no diagrama causal e a partir deste foi elaborado o diagrama de estoques e fluxos. Por meio do diagrama de estoques e fluxos se estabeleceu o modelo matemático que possibilitou a simulação numérica. A escala temporal utilizada para as simulações e aplicação do modelo foi determinada pelo ciclo da cultura e permitiu simulações de 2010 até 2100. Buscou-se aderir ao sistema as variáveis mais importantes que tivessem possibilidade de serem quantificadas, objetivando resultados que se aproximassem à realidade. De modo geral os resultados obtidos pelo modelo desenvolvido mostram que a elevação das concentrações de CO2 na atmosfera combinadas com temperatura do ar, maiores, menores ou iguais às que geralmente ocorrem em ambiente natural, promoverão maior eficiência do uso água pela laranjeira. Outros fatores foram adicionados, como a deficiência hídrica no solo, e verificou-se que, o parâmetro produtividade da água na condição não irrigada será consideravelmente inferior a situação irrigada em 2100. Na área irrigada ...
Dynamic system modeling systemic to analyze the effect of climate change on natal orange water productivity in São Paulo State
Keywords: Modelos matematicos; Laranja; Recursos hídricos - Desenvolvimento; Produtividade agrícola; Mudanças climáticas; Mathematical models